190 Brain Structural MRI Predicts Outcome of Radiosurgical Treatment in Trigeminal Neuralgia. (1st April 2022) - Albano, Luigi; Agosta, Federica; Basaia, Silvia; Castellano, Antonella; Messina, Roberta; Parisi, Veronica; Barzaghi, Lina R.; Falini, Andrea; Mortini, Pietro; Filippi, Massimo
Abstract : INTRODUCTION: Growing evidence supports the role of the central nervous system (CNS) in the modulation of pain in trigeminal neuralgia (TN) patients. METHODS: Thirty patients with idiopathic or classic TN, who underwent GKSRS and were followed for at least 24 months, were retrospectively included. Pre-treatment structural MRI and pre- and serial, post-operative clinical features were investigated. Fifteen age- and sex-matched healthy controls were also enrolled. Cortical thickness and gray matter (GM) volumes were assessed in TN patients relative to controls, as well as between patient subgroups according to treatment outcomes (initial responders/non-responders, patients with pain recurrence/long-lasting pain relief at the last follow-up). Clinical and MRI predictors of treatment outcomes were explored. RESULTS: Cortical thinning of temporal, prefrontal, cingulate, somatosensory and occipital areas bilaterally was found in TN patients relative to controls. No cortical thickness and GM volume differences were observed when TN initial responders and non-responders were compared. Patients who experienced TN recurrence after initial pain relief were characterized by thicker parahippocampal and temporal cortices bilaterally and greater volume of right amygdala and hippocampus compared to patients with long-lasting pain relief. In TN patients, disease duration and baseline cortical thinning of right parahippocampal, left fusiform and middle temporal cortices were associated with poor outcome after GKSRS at the last follow-up (R2 = 0.57, p < 0.001). CONCLUSION: The study provides novel insights into structural brain alterations of TN patients, which might contribute to disease development and pain maintenance.